LENS GLUTATHIONE, LENS PROTEIN GLYCATION AND ELECTROPHORETIC PATTERNS OF LENS PROTEINS IN STZ INDUCED DIABETIC RATS - (:unkn) unknown (CHAPMAN HALL LTD, 1995)
As diabetes is a very complex disease, with the pathological symptoms varying with age, diabetic type and means of control, it still warrants many in vivo and in vitro studies. During hyperglycaemia, increases in the sorbitol pathway, nonenzymatic glycosylation of lens proteins and damage to antioxidant systems have been reported to cause opacification of the lens leading to cataract formation. In this study, intracapsular extracts of lenses from STZ induced diabetic female rats were examined. Total protein, glutathione and nonenzymatic glycosylation were determined by the Lowry, Ellman reagent and thiobarbituric acid methods respectively. Laemmli protein electrophoresis was also carried out on the lens homogenates. After a period of as short as 5 weeks, a decrease in lens glutathione, and an increase in nonenzymatic glycosylation of lens proteins were found. The electrophoresis showed an increase in proteins of high molecular weight.
Keywords: LENS; DIABETES; GLUTATHIONE; NONENZYMATIC GLYCOSYLATION; ELECTROPHORESIS; ALDOSE REDUCTASE; CATARACTOGENESIS; CRYSTALLINS; GLUCOSE; GLYCOSYLATION; INVITRO